Dampak ketidakpuasan konsumen pada sikap konsumen berdasarkan dimensi kualitas jasa dan perbedaan karakteristik demografi - Anis Hidayah; Sumiyarsih Sumiyarsih (Universitas Mercu Buana Yogyakarta, 2018)
The purpose of this paper is to test the effect of dissatisfaction consumers that influence on negative customer behavior, base on demography and service quality. Design/methodology/approach, An integrated model is proposed, following recent developments in the service recovery literature. This model is tested using data from a survey with 216 customers. The paper reports results from structural aquation model. Findings, the results show significant influence service quality, demography and dissatisfaction customer have significant effect to negative customer behavior.